Study on global economic efficiency in Romanian agriculture - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
This paper aims to analyze the economic efficiency at the macroeconomic level of the agricultural sector in Romania, in order to determine the level of profitability or feasibility regarding this economic sector, respectively agriculture. In order to be able to determine the global economic efficiency in the agriculture of Romania, first of all, indicators of the Economic Accounts from Agriculture will be analyzed, found in the national data bases, respectively the National Institute of Statistics; and, secondly, with the help of these indicators, a calculation system will be developed to determine the overall economic efficiency of the Romanian agricultural sector. Determining the level of profitability of agriculture is very important considering the context of globalization and the development of competitive markets, in order to have access to the market, the level of competitiveness can be measured by this analysis, mentioned above.
Keywords: Q10; Q11; 330; agriculture; competitiveness; economic efficiency; performance; profitability